Ancient Enemy: Leprosy in India - ALJAZEERA and Lifelines India (My University, 2014)
This is the story of health workers like Rajni Kant Singh and others and their fight for tackling the deeply rooted stigma, social, medical and psychological aspects associated with leprosy. Leprosy was declared officially eliminated in 2005 by the government of india. Consequently, it slipped off the agenda and resources has been constrained. However, it persists in India and stigma remains a huge obstacle to diagnosis and treatment. This film also documents the story of Rachna Kumari- a Leprosy counsellor and social isolation she faced before her treatment.
Documentary available at: https://www.aljazeera.com/program/lifelines/2014/5/22/ancient-enemy-leprosy-in-india
Keywords: People with Leprosy